A atuação do Programa Amparando Filhos na defesa dos direitos dos(as) filhos(as) das presas da Comarca de Itumbiara-GO - Moreira, Simone Gonçalves (2022)
This work intends to analyze whether the Amparando Filhos Program fills the gaps in public policies aimed at the children of incarcerated mothers, who are in their company in the prison unit or are in a foster family in the District of Itumbiara, and to verify, based on interviews conducted, the effectiveness of your actions. Therefore, was considered the period of activity of the researcher as a forensic social worker who has followed the program since its implementation in Itumbiara, in December 2016,bibliographic survey, document research, interviews and observations in order to verify if there are and what are the public policies focused on guaranteeing the rights of these children, the gaps and the need for its implementation, contextualizing the woman and her insertion into the criminal world; the situation of the mother who is incarcerated; about the children who stay with the mother in the prison unit; talk about the physical and affective distancing of incarcerated mothers and their children, as well as about the new caregivers for these children, as, at first, they are under the guardianship by grandmother or maternal aunt, and in this perspective, to verify that care still remains focused on the female figure, and to analyze the effectiveness of the actions of the Amparando Filhos Program according to the interviews conducted.